Relationship Between The Effectiveness Of Commucation In The Family with The Intensity Of The Use Of Early Childhood Gadgets In Kenagarian Pasar Baru Pesisir Selatan Regency - Okta Pratama, Silvia; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research was motivated by the high intensity of playing with gadgets from early childhood in Kenagarian Pasar Baru, Pesisir Selatan Regency. The method used in the research is a quantitative approach with a correlational type. The population of this study was 52 parents who had children aged 3-6 years. The data collection method used is a questionnaire which contains statements that are used as a data collection tool. Next, the data was analyzed using a percentage formula with correlation using the Product Moment formula. The results of the research show that: (1) the effectiveness of communication in the family is classified as poor, (2) the intensity of gadget use in early childhood in Kenagarian Pasar Baru, Pesisir Selatan Regency is classified as high, and (3) there is a significant relationship between the effectiveness of communication in the family and the intensity of communication in the family. Early childhood gadget use in Kenagarian Pasar Baru, Pesisir Selatan Regency. Keywords: effectiveness of family communication, intensity of gadget use